Widespread Dietary Patterns (Healthy and Balanced Diet, Western Diet, and Vegan and Vegetarian Diets) Compared for Water Consumption: Which Is the Winner? - Virginia Vettori (MDPI AG, 2021)
An increasing number of people are interested in following a dietary pattern that is environmentally sustainable and water saving. However, consumers are mostly unable to recognize evidence-based information on food and nutrition and efficiently manage their diet. We conducted a narrative review aiming to support professionals to guide their assisted people that decide to follow a dietary pattern chosen for environmental or ethical reasons. We reviewed three scientific databases and Google Scholar, searching for papers that deal with the water consumption of widespread and well known dietary patterns (Healthy and Balanced Diet, Western Diet, and Vegan and Vegetarian diets). Our results suggest that moving toward a low-animal-based diet favors a reduction in water consumption, but current evidence is not sufficient to establish which is the winner in terms of water saving by comparing Vegetarian and Vegan diets.